2022
DOI: 10.1186/s13063-021-05985-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 and calcium carbonate supplementation for adolescents with HIV to reduce musculoskeletal morbidity and immunopathology (VITALITY trial): study protocol for a randomised placebo-controlled trial

Abstract: Background Of the 2 million children living with HIV globally, 90% live in sub-Saharan Africa. Despite antiretroviral therapy, longstanding HIV infection is associated with several chronic complications in children including growth failure, particularly stunting and delayed puberty. Vitamin D deficiency, which is highly prevalent among children living with HIV in sub-Saharan Africa, has a further adverse impact on bone health. This trial aims to establish whether supplementation with vitamin D3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In recent years, with the improvement of people' understanding of the function of calcium in human physiology, it is believed that the occurrence of gestational hypertension may be associated with calcium [ 7 ]. Clinical research has found that the calcium requirement of the maternal body increases significantly at about 20 weeks of gestation [ 8 ], and at about 30 weeks, the calcium requirement of the maternal body can be about 6 times higher than that at 20 weeks, so the maternal body is prone to calcium deficiency in the second trimester [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the improvement of people' understanding of the function of calcium in human physiology, it is believed that the occurrence of gestational hypertension may be associated with calcium [ 7 ]. Clinical research has found that the calcium requirement of the maternal body increases significantly at about 20 weeks of gestation [ 8 ], and at about 30 weeks, the calcium requirement of the maternal body can be about 6 times higher than that at 20 weeks, so the maternal body is prone to calcium deficiency in the second trimester [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in one study of vitamin D supplementation trial among 81 CWH in the USA, an improvement in jump power was observed, albeit in an exploratory post hoc analysis [42]. Whether vitamin D supplementation can improve muscle function in African CWH is currently subject to clinical trial [43].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in one study of vitamin D supplementation trial among 81 CWH in the USA, an improvement in jump power was observed, albeit in an exploratory post hoc analysis [42]. Whether vitamin D supplementation can improve muscle function in African CWH is currently subject to clinical trial [43]. In male individuals, lower muscle density (indicating greater intramuscular fat) partially mediated the negative effect of HIV infection on jump power.…”
Section: Discussionmentioning
confidence: 99%